2016
DOI: 10.1364/ol.41.001360
|View full text |Cite|
|
Sign up to set email alerts
|

Tapered polysilicon core fibers for nonlinear photonics

Abstract: We propose and demonstrate a novel approach to obtaining small core polysilicon waveguides from the silicon fiber platform. The fibers were fabricated via a conventional drawing tower method and then subsequently tapered down to achieve silicon core diameters of ~1 µm, the smallest optical cores for this class of fiber to date. Characterization of the material properties have shown that the taper process helps to improve the local crystallinity of the silicon core, resulting in a significant reduction in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…This is due both to the larger core sizes of the as-drawn MCD fibers, where typical diameters are tens to hundreds of microns [4], [12], as well as the higher losses associated with scattering and absorption at the grain boundaries in the polycrystalline material [14]. To address these issues, a novel tapering procedure has been developed to post-process the as-drawn fibers [27]. As well as reducing the core size of the fibers, the procedure also acts to improve the overall crystallinity of the core by enhancing the grain growth and aligning the crystal orientation with respect to the fiber axis [28].…”
Section: Polysilicon Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due both to the larger core sizes of the as-drawn MCD fibers, where typical diameters are tens to hundreds of microns [4], [12], as well as the higher losses associated with scattering and absorption at the grain boundaries in the polycrystalline material [14]. To address these issues, a novel tapering procedure has been developed to post-process the as-drawn fibers [27]. As well as reducing the core size of the fibers, the procedure also acts to improve the overall crystallinity of the core by enhancing the grain growth and aligning the crystal orientation with respect to the fiber axis [28].…”
Section: Polysilicon Fibersmentioning
confidence: 99%
“…Using this tapering procedure, a number of low loss (∼ 1 − 4 dB/cm) p-Si fibers have been demonstrated with core sizes in the range 900 nm − 4 µm [27], [29]. Fig.…”
Section: Polysilicon Fibersmentioning
confidence: 99%
“…Subsequently, the nonlinear transmission [127], two-photon absorption (TPA) [128], cross-phase modulation (XPM) [129], four-wave mixing (FWM) and super-continuum generation (SC) [130] all have been investigated. As nonlinear effects generally are enhanced at small core sizes, tapering of the fiber also has been employed and has yielded soliton generation [131] and the first observation of nonlinear transmission within a polycrystalline silicon waveguide of any type [132].…”
Section: Semiconductor Core Optical Fibersmentioning
confidence: 99%
“…Comprehensive material and structural characterization of the tapered SCFs has shown that the tapering process can also act to enhance the crystalline quality of the core through increasing the grain sizes [15] and aligning the crystallographic orientation with the fiber axis [16]. In addition, tapering has been utilized to decrease core diameters of asproduced SCFs down to sub-micron scales for dispersion engineering and mode field area reduction in nonlinear optical applications [17].…”
Section: Introductionmentioning
confidence: 99%